Towards Global DEM Generation by Combining GEDI and Icesat-2 Data - Tian, Xiangxi; Shan, Jie (IEEE International Geoscience and Remote Sensing Symposium proceedings, 2023)
Widely used in geoscience, global or large-scale digital elevation model (DEM) is an essential depiction of the 3-dimenional information of the bare earth [1] . Among others, the most popular DEMs include the Shuttle Radar Topography Mission (SRTM) DEM (1" for USA and 3" for global), ASTER GDEM (30m), and several other similar ones [1] . The most significant problem for these existing global DEMs is the temporal latency (more than 20-year-old for SRTM [2] , more than 10-year-old for ASTER [3] ). Furthermore, some of these foundation data lack consistencies due to the inclusion of multiple data sources collected over a long period of time [1] . The successful launches of the Global Ecosystem Dynamics Investigation (GEDI) mission in December 2018 [4] and the Ice, Cloud, and land Elevation Satellite-2 (ICESat-2) mission [5] in September 2018 provide current, complementary, and dense on-orbit global elevation with unprecedented accuracy and coverage in the history of space laser altimetry. However, many researchers have found that GEDI and ICESat-2 data have inconsistent quality, e.g., a root mean square error (RMSE) of 4.48 m for GEDI terrain height [6] and an uncertainty ranging from 0.2 m to 2 m for ICESat-2 ATL08 terrain height [7] . Beyond the abundant research focusing on quality assessment, there are a significant amount of work on wall-to-wall mapping by integrating GEDI and other Earth observations to overcome the spatial heterogeneity of spaceborne lidar data [8] - [11] . However, there are no recent studies to generate terrain height using GEDI since it is originally designed for forestry studies; and the capability and accuracy of its terrain measurements are less promising than canopy measurements [6] , [7] . Subsequently, few research was reported to combine the terrain measurements from GEDI and ICESat-2 to achieve an even denser coverage than using GEDI or ICESat-2 alone.